Optimasi Produktivitas Alat Angkut Berdasarkan Produksi Bijih Emas Pada Volumetric Loader Crushing Plant - Pristanto, Fahreza Nanda; Ardyansyah, Muhammad Bayu; Aminah, Siti; Haeruddin, Haeruddin; Suparno, Fanteri Aji Dharma (Jurnal Teknologi Sumberdaya Mineral, 2024)
Hauling is a very important process in the mining industry. Transport activities are not only carried out at the mine front, but there is also the transport of processed materials such as transporting gold ore from the crushing plant to the dumping area. The heavy equipment used in this process is divided into two, namely loading equipment and transportation equipment. The loading equipment used is a volumetric loader, while the transportation equipment used is a medium dump truck with a vessel capacity of 40 tons. This moving activity certainly requires determining the number of transport equipment to balance the productivity of the loading equipment used by analyzing the units used. Productivity analysis is very necessary to determine the achievement of a production which will also be influenced by the match factor between loading equipment and transportation equipment. The data used in the productivity analysis include gold ore production from the crushing plant, dump truck specifications, transportation equipment circulation time, obstacle time, and working hours obtained based on observations in the field. Determining the number of transport equipment units to serve the production of loading equipment has been carried out, but conditions in the field sometimes still result in queues of transport equipment and idle loading equipment. This resulted in the production target of moving gold ore not being achieved. Factors in the field that can influence include unfavorable weather and climate, the need for mechanical equipment operators and equipment repairs during operating hours. This has an impact on reducing the level of production achievement. The productivity results obtained by assuming that the resistance time factor was eliminated resulted in an increase in productivity of 9.78% compared to actual productivity, with an optimal number of dump trucks totaling 11 units. Keywords: hauling, productivity, match factor, resistance time